On the nature of ionic liquid gating of Nd₂CuO₄ thin films - Atesci, Hasan; Coneri, Francesco; Leeuwenhoek, Maarten; Hilgenkamp, Hans; Jan M. van Ruitenbeek (Физика низких температур, 2017)
Recently, ionic liquid gating has been used to modulate the charge carrier properties of metal oxides. The mechanism behind it, however, is still a matter of debate. In this paper, we report experiments on doped and undoped Nd₂CuO₄. We find major resistance drops of the bilayer coupled to observations of the presence of a considerable Faradeic component in the gate current and of the appearance of charge transfer peaks in the cyclic voltammetry data. This leads us to propose a mechanism of gating based on irreversible electrochemical reactions, likely due to trace amounts of contaminations present in the ionic liquid. This work is therefore in line with previous reports confirming the presence of irreversible electrochemistry in ionic liquid gated electron- doped cuprates.